Photoinduced Tandem Cyclization of Alkynes with Phenylsulfinic Acids: Access to Sulfone-Substituted Dioxodibenzothiazepines or Dibenzazepines - Chen, Shiliu; Yan, Qinqin; Fan, Jie; Li, Lijun; Liu, Zhong-Quan; Li, Zejiang (Synlett, 2022)
Photoinduced tandem cyclization of alkynes with phenylsulfinic acids has been accomplished, which gives a mild strategy for the preparation of sulfone-substituted seven-membered N-heterocycles. A variety of scaled-up experiments, further transformations, and mechanistic studies were also operated in the follow-up work.
Keywords: photoinduced; tandem cyclization; alkynes; sulfone; seven-membered N-heterocycles